Essential drug list for cardiovascular diseases in a tertiary health care centre - Maddali, Varshini Lakshmi Tripura; Shashidhar, Manali; Narasimhaiah, Manjunath G.; Ramesh, Harshith (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Essential medicines are those that satisfy the priority health care needs of a population. The latest version of NLEM is the 23rd list, published in September 2022, and contains 384 essential drugs, of which 29 are cardiovascular drugs. The drugs in the list may be huge or small according to the local needs. The objectives of our study are to prepare the essential drug list for cardiovascular disease in a tertiary care hospital and to confirm the essential drug list provided and its availability in the pharmacy. Methods: We interviewed around 28 consultants from various departments who prescribe these cardiac drugs. The names, doses and dosage forms were noted. The list was verified with the NLEM 2022 and counterchecked in the hospital pharmacy. Results: Most consultants adhered to NLEM, but an additional 42 drugs were prescribed, amounting to 71 drugs. There are four drugs Warfarin, Rivaroxaban, Furosemide and Torsemide which may be considered for the hospital pharmacy list. Conclusions: Too many drugs other than those present in the NLEM list are prescribed, which can be reduced by adequately training the consultants to adhere to the prescribed list.